Estimating Gender Differences in Access to Jobs - Gobillon, Laurent; Meurs, Dominique; Roux, Sébastien (Journal of Labor Economics, 2015)
This paper proposes a new measure of gender differences in access to jobs based on a job assignment model. This measure is the probability ratio of getting a job for a female and a male at each rank of the wage ladder. We derive a nonparametric estimator of this access measure and estimate it for French full-time executives aged 40–45 in the private sector. Our results show that the gender difference in the probability of getting a job increases along the wage ladder from 9% to 50%. Females thus have a significantly lower access to high-paid jobs than to low-paid jobs.